INTEGRITASI NILAI FILSAFAT PENDIDIKAN ISLAM DALAM PEMANFAATAN TEKNOLOGI DIGITAL BAGI GENERASI Z DAN ALPHA - Mulia Sopiandi Harahap; Ahmad Fauzi Hasibuan; Herlini Puspika Sari (Universitas Negeri Medan, 2025)
This study aims to examine Islamic educational philosophy approaches that are relevant to the challenges of shaping the character of Generations Z and Alpha in the digital age.. The main issue examined is the occurrence of value disorientation and moral degradation due to the massive penetration of technology in educational life. The purpose of this study is to formulate a technology-based Islamic education concept grounded in the values of tawhid, akhlak, and hikmah. The research method used is qualitative with a descriptive analytical approach through literature study and critical review of previous research results. The results show that the integration of Islamic values in educational technology can create a balance between spiritual intelligence and digital competence. Islamic educational philosophy acts as an ethical guide that directs the use of technology towards the formation of Qur'anic character, digital competence, and civility. This study confirms that technology-based Islamic education has great potential in shaping a generation that is adaptive, innovative, and noble in character in the digital age.